Karakter Komunikasi Interkultural Presiden Joko Widodo di Masa Pandemi Indonesia - Rahmadani, Shofia (Universitas Nahdlatul Ulama Blitar, 2024)
The stuttering in handling this pandemic communication has caused serious problems such as the perceived lack of good governance of the Indonesia Maju cabinet under the leadership of President Jokowi, weak coordination between ministries, institutions, and local governments. This research explains the analysis of President Jokowi's communication and the resulting policies during the Covid-19 Pandemic. This research uses a descriptive qualitative method by using book literature studies, and a collection of news on social media.